A Caza de Don Celinos - Mariño Ferro, Xosé Ramón (Madrygal. Revista de Estudios Gallegos, 2005)
We analyze the Galician version of “The hunt of don Celinos”, a ballad about adultery. The Galician version works out to be fairly enigmatic, since the wife tells her husband that if he doesn’t bring a deer’s head, she will have an abortion. To clarify the enigma, we trace the significance of the deer in the traditional European culture